2011
DOI: 10.1002/app.33636
|View full text |Cite
|
Sign up to set email alerts
|

Cationically cured natural oil‐based green composites: Effect of the natural oil and the agricultural fiber

Abstract: Green composites were produced from various cationically cured natural oil-based resins and agricultural fibers. The natural oils and agricultural fibers of interest included corn, soybean, fish, and linseed oils and corn stover, wheat straw (WS), and switchgrass fibers. The effects of the types of natural oil and agricultural fiber on the structure and thermal and mechanical properties of the composites were studied using Soxhlet extraction, thermogravimetric and dynamic mechanical analysis, and tensile testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Pfister and Larock presented an interesting comparison of the behavior of different cationically cured plant oils used as matrices of agricultural fibers [113]. They considered composites prepared from corn, soybean, fish, and linseed oils using up to 75 wt% of different natural fibers, corn stover, wheat straw, and switch-grass fibers.…”
Section: Compositementioning
confidence: 99%
“…Pfister and Larock presented an interesting comparison of the behavior of different cationically cured plant oils used as matrices of agricultural fibers [113]. They considered composites prepared from corn, soybean, fish, and linseed oils using up to 75 wt% of different natural fibers, corn stover, wheat straw, and switch-grass fibers.…”
Section: Compositementioning
confidence: 99%
“…Furthermore, other similar resins containing 45 wt % of a variety of conjugated vegetable oils have been consistently prepared, and yielded materials with interesting thermo-mechanical properties [4]. It has also been shown that when vegetable oils are cationically co-polymerized with mixtures of DVB and ST, a homogeneous material is obtained [4].…”
Section: Resin Compositionmentioning
confidence: 99%
“…Furthermore, other similar resins containing 45 wt % of a variety of conjugated vegetable oils have been consistently prepared, and yielded materials with interesting thermo-mechanical properties [4]. It has also been shown that when vegetable oils are cationically co-polymerized with mixtures of DVB and ST, a homogeneous material is obtained [4]. In a related work, evaluating the concentration of DVB in conjugated vegetable oil-based resins cured by free radical polymerization, it has been shown that samples containing 15 wt % of DVB exhibit good mechanical properties [5].…”
Section: Resin Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, numerous vegetable oil-based thermosetting resin systems have been recently studied [1][2][3][4][5][6]. Vegetable oil-based resins recently developed include polyester amides [7], and cyanate esters [8].…”
Section: Introductionmentioning
confidence: 99%